Efficacy of dehydroepiandrosterone to improve ovarian response in women with diminished ovarian reserve: a meta-analysis - Narkwichean, Amarin; Maalouf, Walid; Campbell, Bruce K.; Jayaprakasan, Kannamannadiar (BioMed Central, 2013)
Women with diminished ovarian reserve often respond poorly to controlled ovarian stimulation resulting in retrieval of fewer oocytes and reduced pregnancy rates. It has been proposed that pre-IVF Dehydroepiandrosterone (DHEA) adjuvant therapy may improve ovarian response and pregnancy rates in women with diminished ovarian reserve. This meta-analysis aims to investigate efficacy of DHEA as an adjuvant to improve ovarian response and IVF outcome in women with diminished ovarian reserve. Electronic databases were searched under the following terms: (DHEA) and (diminished ovarian reserve) and/or (poor response). Studies were included if they reported at least one of the following outcomes; clinical pregnancy rate, number of oocytes retrieved, miscarriage rate. We identified 22 publications determining effects of DHEA in clinical trials. Only 3 controlled studies were eligible for meta-analysis. There was no significant difference in the clinical pregnancy rate and miscarriage rates between women pre-treated with DHEA compared to those without DHEA pre-treatment (RR 1.87, 95% CI 0.96-3.64; and RR 0.59, 95% CI 0.21-1.65, respectively). The number of oocytes retrieved (WMD -1.88, 95% CI -2.08, 1.67; P < 0.001) was significantly lower in the DHEA group. In conclusion, based on the limited available evidence from a total of approximately 200 IVF cycles, there are insufficient data to support a beneficial role of DHEA as an adjuvant to controlled ovarian stimulation in IVF cycle. Well-designed, randomised controlled trials as well as more exact knowledge about DHEA mechanisms of action are needed to support use of DHEA in standard practice for poor-responders.